PHYSICAL FITNESS AND MORPHOFUNCTIONAL STATUS OF BOYS AGED 6-8 YEARS - Abramova, T.F.; Nikitina, T.M.; Polfuntikova, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the relationship between the morphofunctional status and physical fitness in modern boys aged 6-8 years. Methods and structure of the study. The work used standardized methods for assessing physical development and physical fitness. Morphofunctional status was determined using the methods of anthropometry, caliperometry, spirometry, pulsometry and tonometry [1,4]. Physical fitness was assessed based on the results of test tasks, used in the field of physical education and VFSK "GTO": 30 m run; shuttle run, 3 × 10 m (s); 6-minute run (m); standing long jump with two legs (cm); standing forward bend (flexibility, cm); carpal dynamometry, flexion and extension of the arms in an emphasis lying on the floor, lifting the torso into a sitting position from a supine position in 1 min [2,3]. Results and conclusions. Based on a comparative analysis of the level and pace of morphofunctional development and preparedness, it was revealed that the indicators of morphofunctional status and physical fitness differ significantly among boys aged 6 and 7, 7 and 8; the greatest increase in physical fitness with the priority of speed-strength qualities and endurance is typical for the period from 6 to 7 years, with a decrease in rates in the period from 7 to 8 years on average twice against the background of relatively uniform and lower rates of annual changes in morphological and functional indicators. The results obtained indicate that the standards of physical fitness for boys of age groups of 6, 7 and 8 years old, characterized by normal physical development, should be developed for each age group, taking into account the greatest coverage of territorial variability.